Pathogenicity assessment and whole-genome sequencing of Salmonella abortus equi strain XJ2032 isolated from Xinjiang, China - Fu, Han; Li, Tongyang; Wang, Yuyan; Yang, Yang; Lu, Yabin; Li, Jianlong; Liu, Jianhua; Kuang, Ling; Mai, Zhanhai; Guo, Qingyong (Frontiers in Veterinary Science, 2025)
IntroductionEquine abortus salmonellosis, caused by Salmonella abortus equi (S. abortus equi), is a contagious disease primarily characterized by abortion in pregnant equine animals. Due to its high pathogenicity and increasing incidence, this disease has attracted significant scientific attention. While the causes of abortion in mares are multifactorial and may involve numerous pathogenic factors, the specific impact of S. abortus equi on the vaginal microecological environment and its pivotal role as the primary causative agent of abortion remain poorly understood.ResultsFurther analysis led to the successful isolation and identification of S. abortus equi from vaginal samples of aborted mares. A highly pathogenic isolate, designated as XJ2032, was selected for further analysis. To gain a more profound understanding of the functional genomic composition and genetic traits of this strain, whole-genome sequencing was conducted, and sophisticated bioinformatics techniques were employed to predict and annotate its gene sequences. Furthermore, animal model experiments, and PCR-based molecular biological detection methods were utilized to assess the virulence and drug resistance genes of the isolated strain XJ2032, further confirming its pathogenic potential.ConclusionWhole-genome sequencing analysis confirmed that strain XJ2032 is indeed S. abortus equi. Although its genome structure is largely conserved, some rearrangements and inversions were identified. The strain harbors multiple virulence genes and drug resistance genes, including horizontally transferable genes and mobile genetic elements. These findings suggest that genomic islands and bacteriophages play a vital role in the pathogenicity and genetic diversity of S. abortus equi.